ABSORPTION POTENTIAL IN INCREASING INNOVATIVE PERCEPTION OF KAZAKHSTAN ENTERPRISES - G. Alibekova; N. Ainakul; M. Bapiyeva (Scientific Journal of Pedagogy and Economics, 2019)
Currently, for the development of society and economic growth, new technologies built on new ideas and new knowledge play an important role. It should be noted that the potential of existing industries, despite the task of transferring the economy to an innovative development path, currently requires substantial growth in all areas: strategic, managerial, organizational, technical and technological, personnel. Analysis of the current situation by various indicators showed the inertia of the innovative development of enterprises in Kazakhstan. The purpose of the study is to conduct a review of the scientific literature and the development of approaches to increase the innovative activity of enterprises. The results of the study show that one of the factors for increasing the innovation susceptibility and absorption capacity of enterprises, leading to the growth of innovative activity, is the network interaction of enterprises. Сhannels of network interaction were analyzed and were proposed the expansion of network interaction of enterprises through the development of an informal information channel and human resources channel to increase the absorption capacity of low and medium technological enterprises, and expansion of interaction with universities and scientific organizations through the development of a channel of research projects and consulting to support the development of high-tech enterprises. It is assumed that the development of network interaction will enhance the absorption potential of enterprises, and, accordingly, their susceptibility to innovative solutions and technologies.